Optimization of Spiral-Based Pulse Sequences for First Pass Myocardial Perfusion Imaging - Salerno, Michael (2011)
While spiral trajectories have multiple attractive features such as their isotropic resolution, acquisition efficiency, and robustness to motion, there has been limited application of these techniques to first pass perfusion imaging because of potential off-resonance and inconsistent data artifacts. Spiral trajectories may also be less sensitive to dark-rim artifacts (DRA) that are caused, at least in part, by cardiac motion. By careful consideration of the spiral trajectory readout duration, flip angle strategy, and image reconstruction strategy, spiral artifacts can be abated to create high quality first pass myocardial perfusion images with high SNR. The goal of this paper was to design interleaved spiral pulse sequences for first-pass myocardial perfusion imaging, and to evaluate them clinically for image quality and the presence of dark-rim, blurring, and dropout artifacts.